2019
DOI: 10.1001/jamaophthalmol.2018.4229
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Uncorrected Refractive Error in Older Adults in a Population-Based Study in France

Abstract: IMPORTANCE Uncorrected refractive error (URE) is a common cause of visual impairment, but its prevalence in groups of older adults who could be pragmatic targets for improving optical correction remains unknown. OBJECTIVES To estimate the prevalence of URE in older adults, particularly in those with age-related eye disease and those who are unable to attend an outpatient clinic, and to identify the factors associated with URE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Although with these differences, the URE in the present urban Chinese population is quite high (7.9%; 95% CI, 7.13-8.58%). Consistent with the previous studies, we observed higher URE in the older individuals (30,35). Females demonstrated higher…”
Section: Discussionsupporting
confidence: 92%
“…Although with these differences, the URE in the present urban Chinese population is quite high (7.9%; 95% CI, 7.13-8.58%). Consistent with the previous studies, we observed higher URE in the older individuals (30,35). Females demonstrated higher…”
Section: Discussionsupporting
confidence: 92%
“…These results need to be replicated in other large longitudinal studies with both measure of near and distance visual acuity, and potential mediators need to be further explored. A large part of VL is correctable or preventable [46] . However, future researches and interventional studies are needed to further evaluate whether VL is only an indicator of future dementia or whether the improvement of VL, may represent a promising opportunity for dementia prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on URE in the elderly including a study that we conducted in the home for the aged in Prakasam district in India 4,11,16‐20 . From a nursing home‐based study in the United States, Tielsch reported that 54% of the participants improved their presenting visual acuity on best correction with about 8% improving by three or more lines on the letter chart 11 .…”
Section: Discussionmentioning
confidence: 99%